On the compatibility of bureaucracy and development administration - Huque, Ahmed Shafiqul (1985)
Bureaucracy has been defined in various ways, mostly from the point of view of western scholars. But the nature of bureaucracy and administrative activities are markedly different in developing countries, and often, there seem to be several contradictions between the concepts of bureaucracy and development administration. There is, no doubt, a need to redefine bureaucracy on the basis of the experience of developing countries and to decide on the groups that may be included in this category. While bureaucracy is not entirely incompatible with development administration, some of its features need modifications to suit the circumstances prevailing in developing countries. But the most important requirement is a set of parallel political institutions which will provide the crucial balance in the system to make bureaucracy an effective tool in the process of development administration.
Keywords: Bureaucracy; Public administration